2016
DOI: 10.25100/cm.v47i1.2085
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of kidney transplants on patients with end-stage renal disease secondary to lupus nephritis, polycystic kidney disease and diabetic nephropathy

Abstract: Background: Patients with lupus nephritis could progress to end-stage renal disease (10-22%); hence, kidney transplants should be considered as the treatment of choice for these patients. Objective: To evaluate the clinical outcomes after kidney transplants in patients with chronic kidney diseases secondary to lupus nephritis, polycystic kidney disease and diabetes nephropathy at Pablo Tobon Uribe Hospital. Methods: A descriptive and retrospective study performed at one kidney transplant center between 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…Renal transplantation is a viable treatment option for patients with end-stage CKD and LN 36 , and the risk of graft failure is similar in renal transplantation patients with and without SLE 5,6 . Moreover, the rates of LN-related complications and recurrence are low 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Renal transplantation is a viable treatment option for patients with end-stage CKD and LN 36 , and the risk of graft failure is similar in renal transplantation patients with and without SLE 5,6 . Moreover, the rates of LN-related complications and recurrence are low 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic nephropathy (DN) is one of the most common complications of diabetes mellitus (DM) which leads to end-stage renal failure in 30%–40% of DM patients. 1 3 The incidence of DN will rapidly increase with increase in the incidence of DM in China in the decades to come. 4 , 5 Oxidative stress injury and TGF-β/Smads signal transduction are vital to the development and progression of DN.…”
Section: Introductionmentioning
confidence: 99%
“…However, concerns have arisen about potentially worse outcomes after renal transplant among patients with LN-ESRD, relating to certain SLE features and associated treatments (10,11,(25)(26)(27). For example, some studies (although not all [28][29][30]) have suggested higher rates of allograft failure among patients with LN-ESRD than among those with other causes of ESRD (10,11,25,27). Patients with LN-ESRD may have higher risk for infection due to the intensive immunosuppression used to treat LN and other disease manifestations (31).…”
Section: Discussionmentioning
confidence: 99%